The Integrated Macroeconomic Model for Poverty Analysis : A Quantitative Macroeconomic Framework for the Analysis of Poverty Reduction Strategies - Agenor, Pierre-Richard; Izquierdo, Alejandro; Fofack, Hippolyte (World Bank, Washington, DC, 2014)
The authors present a dynamic, quantitative macroeconomic framework designed for analyzing the impact of adjustment policies and exogenous shocks on poverty and income distribution. They emphasize the role of labor market segmentation, urban informal activities, the impact of the composition of public expenditure on supply and demand, and credit market imperfections. Numerical simulations for a prototype low-income country highlight the importance of accounting for the various channels through which poverty alleviation programs and debt relief may ultimately affect the poor.